The effectiveness of betel leaf (piper betle Linn) extract gel and cocoa bean (theobroma cacao L) extract gel application against the hardness of enamel surface in vitro - Juni J. Nugroho; Wirna R. Hafsari (Journal of Dentomaxillofacial Science, 2017)
Objective : Nowadays several waysÂ  have been evolvedÂ  to increase the hardness of the enamel surface as an effort to prevent caries. One of the alternatives that can be used is application of gel with herbal basic material.Material and Methods : The use of herbal basic material is preferred by people because the side effects are relatively small compared to synthetic drugs. Piper betle and cocoa beans are medicinal plants that is often used by people to inhibit caries. This is because piper betle and cocoa beans contain hardness that may influence the enamel surface. The purpose of this research was to determine the effect of piper betle extract gel and cocoa bean extract gel against the hardness of enamel surface. The samples, maxillary first premolar teeth, which has been extracted and does not have caries, were divided into 3 treatment groups: piper betle extract gel, cocoa bean extract gel, and distilled water as a negative control. Each treatment group consisted of 8 samples. The samples are decoronated in cemento-enamel junction (CEJ) areas and planted on orthoplast blocks with labial surface facing up. Samples were applied in labial enamel surface to 5, 15 and 35 minutes period times. Samples before and after the application in each treatment group were measured using Universal Hardness Tester. Data were collected and analyzed using ANNOVA Repeated test.Results : Showed there were significant differences (p <0.05) of enamel surface hardness before and after the application of cocoa bean extract gel. There were no significant differences (p> 0.05) of enamel surface hardness before and after the application of piper betel extract gel and distilled water.Conclusion : Therefore it can be concluded that cocoa been extract gel is more effective to increase the hardness of email surface.Â